Ensuring security in distributed information systems: major aspects - Yesin, V.I.; Vilihura, V.V.; Svatowsky, I.I. (Radiotekhnika, 2023)
Ensuring the security of distributed information systems is a critical task since these systems are used primarily to process and store large amounts of sensitive information such as financial data, medical records, personal data, etc. Information in the world is one of the most important resources of society, and without its protection, new information technologies can violate the private life of people and activities of various organizations. In the era of Big Data, the problem of protecting sensitive data is even more aggravated. And this is despite the large global security spending that organizations and companies around the world incur, including in order to meet the requirements of relevant laws and other regulations governing the activities of companies in modern conditions. To solve it, it is necessary to use a combination of legislative, organizational measures and software and hardware. Therefore, in the current situation, taking into account: (a) the current state of development of technologies of distributed information systems and its fleeting nature; (b) scientific and practical achievements in the field of information security; (c) the qualifications of attackers who are constantly improving the capabilities of malicious influence; (d) provisions and recommendations of various regulations-legal acts, information systems specialists in many cases, in order to ensure the reliable safe functioning of the latter, need appropriate knowledge of security issues. That is, knowledge of current modern methods, techniques and means of ensuring security. This paper is precisely aimed at providing such knowledge. It concisely presents a fairly wide range of issues related to the security of distributed information systems.